FoMO (Fear of Missing Out) pada Mahasiswa Penggemar Korea : Studi Deskriptif Mahasiswa Pendidikan IPS Fakultas Ilmu Sosial Universitas Negeri Jakarta - Maulidya, Rifi; Safitri, Desy; Istiqomah, Nurul (Program Studi Pendidikan IPS Universitas Negeri Jakarta, 2023)
Globalization has made the development of Korean culture (Hallyu) more rapid in recent years, coupled with advances in technology, causing the emergence of FoMO (Fear of Missing Out), namely the fear or anxiety of missing an event for Korean fans. This study aims to determine the causes and effects of the FoMO (Fear of Missing Out) phenomenon on students who are Korean fans of the Social Sciences Education Study Program, Faculty of Social Sciences, Jakarta State University. The method used in this research is descriptive method with a qualitative approach. The subjects or informants in this study were 10 students using a purposive technique of taking informants with the criteria of Social Sciences Education UNJ students, Korean fans and having moderate to high FoMO scores. To answer the problem formulation, the researcher collected data by distributing pre-research questionnaires, interviews, literature studies, observation and documentation. The results of the study revealed that the cause of FoMO in social studies education students who are Korean fans is the high use of devices and social media. The impact of FoMO on student enthusiasts includes physical impacts; the impact on the psyche; disrupted learning patterns; to finance,. Abstrak Globalisasi membuat perkembangan budaya Korea (Hallyu) semakin pesat beberapa tahun belakang, dengan dibarengi kemajuan teknologi menyebabkan munculnya FoMO (Fear of Missing Out) yakni rasa takut atau cemas tertinggal suatu peristiwa pada penggemar Korea. Penelitian ini bertujuan untuk mengetahui penyebab dan dampak dari fenomena FoMO (Fear of Missing Out) pada mahasiswa penggemar Korea program studi Pendidikan IPS Fakultas Ilmu Sosial Universitas Negeri Jakarta. Metode yang digunakan dalam penelitian ini adalah metode deskriptif dengan pendekatan kualitatif. Subjek atau informan pada penelitian ini berjumlah 10 mahasiswa dengan teknik pengambilan informan purposive dengan kriteria mahasiswa Pendidikan IPS FIS UNJ, penggemar Korea dan memiliki skor FoMO sedang hingga tinggi. Untuk menjawab rumusan masalah peneliti melakukan pengumpulan data dengan cara menyebarkan kuesioner pra penelitian, wawancara, studi pustaka, observasi dan dokumentasi. Hasil penelitian mengungkapkan bahwa penyebab FoMO pada mahasiswa Pendidikan IPS penggemar Korea adalah penggunaan gawai dan media sosial yang tinggi. Adapun dampak dari FoMO pada mahasiswa penggemar antara lain dampak fisik; dampak pada psikis; pola belajar yang terganggu; hingga keuangan.